A TEACHING OF PHYSICAL EDUCATION CLASSES ORGANIZATION IN HIGH SCHOOL: CONTENT AND PLANNING AS MEDIATION ELEMENTS (Fiep Bulletin - online, 2017)
Addressing the didactic organization of school subjects permeates many elements that should include someforms of mediation and among them we can highlight the content, the planning and in the background the Physical Space. Arethese the elements addressed in this article. The curriculum established by SED / MS - Secretary of State of Mato Grosso do SulEducation will serve as a parameter for analysis of some content in its historical perspective associated with the teaching ofphysical education, discipline dealt with in this work. The planning and its historical nuances, the curriculum content and itsimplications for the prospect of physical education classes with the purpose of learning. These elements are part of the didacticorganization and here we will treat of the discipline of physical education content designed for high school and how you can availthe didactic organization by these mediation elements.